PENGETAHUAN PERAWAT TENTANG DEVELOPMENTAL CARE PADA BAYI BERAT LAHIR RENDAH - Hertaty Hotmayda; Tuti Asrianti Utami; Paramitha Wirdani (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2019)
Low birth weight (LBW) infants are infants born with a weight less than or equal to 2500 gramsregardless of the infant's gestational age. LBW infants often have difficulty in transitioning fromintrauterine to extrauterine. Developmental care can facilitate LBW infants in adapting to theirenvironment. LBW infants have generally treated the Neonatal Intensive Care Unit (NICU) and require along period of hospitalization due to the immaturity of immunity. Abnormalities in the process of growthand development are frequently in LBW infants and will affect the quality of life. This study aims todetermine the relationship between characteristics with the knowledge of nurses about developmentalcare in LBW infants. Thirty-eight respondents were included. This study uses the quantitative methodwith the cross-sectional design and descriptive correlation. Data were analyzed using Kendall's Tau B orTau C. The results of this study showed that There isn't a significant correlation between age and nurseknowledge about developmental care in LBW with p-value 0,429,there isn;t a significant relationshipbetween education and nurse knowledge about developmental care on LBW infants with p-value 0,764,there isn?t a significant relationship between the length of work with the knowledge of nurses aboutdevelopmental care in LBW infants with p-value 0.134, there isn't a significant relationship betweentraining with knowledge of nurses about developmental care at LBW infants with p-value 0,879